Belief and perception of international students about the game based-learning Kahoot! and the effects on their academic achievement - Muthi Syahidah Arifuddin (Gema Wiralodra, 2022)
This study aimed to investigating beliefs and perceptions about the use of Kahoot! In the learning process from the research result, the reasons for the effects of their academic achievements would emerge, whether they positively or negatively affect the international students. This research approached was a descriptive qualitative. This approach was used because the theme or research object being studied was related to the empirical condition on the research location, being in line with the qualitative research characteristics. Data were collected In collecting data from the student data in the form of scores obtained in the Kahoot! Previously while studied in the United States. This study used the statement agreement method via a google form, semi-in-depth interviews, and documentation. The data sources of this research were the research subjects' explanations and actions, which included several international students from various countries. For efficiency and effectiveness, informants were selected directly (direct sampling). The results of this study described that their beliefs and perceptions of the Kahoot! were very supportive in the learning process held in the classroom in the United States. They assumed that this application was beneficial in increasing academic achievement with a delightful way of learning. This is proven by their scores of these international students getting very satisfactory results. The specifications includes 8 out of 11 international students who are very enthusiastic about the presence of the Kahoot based-learning game application, followed by their scores increasing from before. On the other hand, three other participants did not recommend this quiz game because it was a little challenging and did not affect their learning effectiveness. The focus of this research was how Kahoot! had a positive effect on increasing student achievement. It could be concluded that Kahoot! Became the most popular application in several countries, especially in the United States of America.